Comparison of Polyurethane-Fluorinated Acrylate Composite Latex Prepared by Two Different Synthesis Technique - Yang, Jianjun; Wu, Qingyun; Jiang, Beibei; Wu, Mingyun; Zhang, Jianan; Wang, Xiaojun (Asian Journal of Chemistry, 2010)
Polyurethane-fluorinated acrylate (FPUA) composite latexes were synthesized from pre-prepared polyurethane seed latex, dodecafluoroheptyl methacrylate (DFMA) and acrylate monomers though monomer pre-emulsification method and monomer dropping method, respectively. Influences of the two different methods on the polymerization stability and the properties of FPUA composite latex film were discussed. The structure of FPUA films were characterized by scanning electron microscopy (SEM) and FT-IR. The mechanical properties of FPUA films were also tested. The results showed that after the incorporation fluorine monomer, fluorinecontaining segments transferred to the surface of the FPUA films and produced phase separation subsequently and FPUA films exhibited improved water and solvent durability, soaking resistance and mechanical properties. Compared with monomer dropping method, FPUA composite latex prepared by monomer pre-emulsification method was more stable.